PENGARUH PENGERINGAN TERHADAP KADAR TANIN TEH HERBAL DAUN BELIMBING WULUH (AVERRHOA BILIMBI) - Azkia Azhara Assya; Owin Ikhlas; Novy Pralisa Putri; Niawanti, Helda (Teknik Kimia ITN Malang, 2022)
Herbal tea is a beverage product that people widely consume to improve health. Herbal teas are processed from various types of plants that contain bioactive compounds. One of the plants that contain bioactive compounds is Averrhoa bilimbi. The drying process is influenced by several parameters, including time and airflow velocity. This study aims to determine the effect of these two parameters on the drying process using a tray dryer on reducing the moisture content and tannin content of herbal tea. Averrhoa bilimbi leaves were dried at 65 ° C, drying times of 60, 90, 120 minutes, and airflow velocities of 6.8, 9.3, and 10 km/hour. The highest air content decreasing was 68%, and the highest tannin content was 1,871 ± 0.283%, which was obtained at an airflow velocity of 6.8 km/hour and a time of 120 minutes. The results showed that the drying time of 120 minutes did not damage the bioactive tannin compounds, and the decrease in air content in the results of drying could increase the levels of tannins extracted when the leaves were brewed into a drink that could be consumed.